IGAD, Sudan, and South Sudan: Achievements and setbacks of regional mediation. Issue 2 (2nd April 2016) - Back, Irit
ABSTRACT: This article aims to review the East Africa regional organization Intergovernmental Authority on Development (IGAD) mediation efforts in Sudan and South Sudan and to contextualize them within the broader context of regionalization in post-Cold War Africa. The idea of using sub-regional organizations to solve interstate conflicts derived from the interwoven phenomena of increasing Western isolationism toward Africa and the growing number of conflicts in the post-Cold War continent. Against this backdrop, the intervention of IGAD in the conflict between northern and southern Sudan in the 1990s and 2000s illustrates how proactive intervention and mediation by a regional organization may contribute to the resolution of intrastate conflicts. IGAD's mediation efforts were in demand again when it turned out that South Sudan's historic achievement of independence was overshadowed by internal strife, which has, since 2013, escalated to a large-scale conflict. In this context, the article will try to explore whether IGAD's accumulated institutional experience over many years of active mediation has marked a new direction of regional activism in East Africa.